2013
DOI: 10.1371/journal.pone.0045519
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Microsatellites on Evolutionary Young Y Chromosome

Abstract: Sex chromosomes are an ideal system to study processes connected with suppressed recombination. We found evidence of microsatellite expansion, on the relatively young Y chromosome of the dioecious plant sorrel (Rumex acetosa, XY1Y2 system), but no such expansion on the more ancient Y chromosomes of liverwort (Marchantia polymorpha) and human. The most expanding motifs were AC and AAC, which also showed periodicity of array length, indicating the importance of beginnings and ends of arrays. Our data indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 48 publications
3
43
2
Order By: Relevance
“…B B chromosome. Bar=5 μm rapidly increasing genomic microsatellite characterization in model and nonmodel species, but studies addressing their characterization at both genomic and chromosomal levels have not virtually been done (Kejnovský et al 2013). We have performed this combined approach in two grasshopper species with genomes of different size, that in E. plorans (11.11 Gb) being almost double that in L. migratoria (6.3 Gb).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B B chromosome. Bar=5 μm rapidly increasing genomic microsatellite characterization in model and nonmodel species, but studies addressing their characterization at both genomic and chromosomal levels have not virtually been done (Kejnovský et al 2013). We have performed this combined approach in two grasshopper species with genomes of different size, that in E. plorans (11.11 Gb) being almost double that in L. migratoria (6.3 Gb).…”
Section: Discussionmentioning
confidence: 99%
“…However, physical mapping by fluorescent in situ hybridization (FISH) constitutes a quicker and easier strategy for ascertaining the abundance and chromosomal distribution of microsatellite and other repeated sequences, thus providing a means for determining, in detail, the precise chromosomal regions in which repeats are clustered, and this is the approach of choice in nonmodel species. The development of NGS technology has highlighted the need for combined genomic and chromosomal analyses for mapping new characterized sequences and confirming de novo genome assemblies, but these combined studies are still scarce (Soltis et al 2013;Kejnovský et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the accepted picture of Y chromosomes, high rates of colonization by DNA satellites prevented a significant expansion of the transposable elements within the Y chromosomes, although some transposable elements were able to compete with satellites for Y-linked niches, either by a higher insertion rate or a lower removal rate . Kejnovský et al [2013] have found evidence of microsatellite expansion on the Y chromosome of R. acetosa in contrast to other older Y chromosomes. They have also found that the abundance of microsatellites is higher in the neighborhood of transposable elements, suggesting that microsatellites are probably targets for insertions of transposable elements [Kejnovský et al, 2013].…”
Section: Satellite Dnas In Plant Sex Chromosomesmentioning
confidence: 91%
“…Kejnovský et al [2013] have found evidence of microsatellite expansion on the Y chromosome of R. acetosa in contrast to other older Y chromosomes. They have also found that the abundance of microsatellites is higher in the neighborhood of transposable elements, suggesting that microsatellites are probably targets for insertions of transposable elements [Kejnovský et al, 2013]. These authors have suggested that microsatellite expansion would be an early event that shaped Y chromosome evolution, while the accumulation of mobile elements and chromosome shrinkage would have occurred later.…”
Section: Satellite Dnas In Plant Sex Chromosomesmentioning
confidence: 91%
“…Our results revealed variability in the distribution of repetitive DNA sequences and their possible association with sex chromosome diversification in Characidium species. © 2015 S. Karger AG, Basel korná et al, 2011; Kejnovský et al, 2013;Milani and Cabral-de-Mello, 2014;Ruiz-Ruano et al, 2015;Ziemniczak et al, 2014]. In this context, cytogenetic studies have provided a better characterization of sex chromosomes by identifying distinctive degrees of heterochromatinization and differential accumulation of repetitive sequences [for a review, see .…”
Section: Chromosomal Mapping Of Repetitive Dnas Inmentioning
confidence: 99%